Empires of the mind : lessons to lead and succeed in a knowledge-based world - Waitley, Denis (Quill New YorkUS, 1995)
Provides several techniques for achieving self leadership, and in the process, taking command of change in the present knowledge era. Emphasises the necessity of maintaining inward focus and supports this conviction by exploring several topics including: change, responsibility, integrity, core values, attitudes, and knowledge.